1993
DOI: 10.1007/bf01973686
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sairei-to on gentamicin nephrotoxicity in rats

Abstract: The effect of Sairei-to, an oriental traditional medicine, against gentamicin nephrotoxicity was examined in gentamicin nephrotoxicity rat models. Gentamicin nephrotoxicity was induced by s.c. injection of gentamicin (100 mg/kg/day, for 3 days) in male Sprague-Dawley rats. Renal functions of two rat groups were compared, one eating rat chow containing 2.5% Sairei-to, the other eating normal rat chow. Sairei-to administration reduced the increase of urinary N-acetyl-beta-D-glucosaminidase (NAG) and protein excr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
(8 reference statements)
1
11
0
Order By: Relevance
“…According to a previous report, an anti‐oxidant, pyrrolidine dithiocarbamate, preventing the degradation of mRNA in cultured pulmonary epithelial cells, increased GM‐CSF expression 23 . It has been demonstrated that the pharmacological effects of Toki and Sai are partly based on their anti‐oxidant action 24,25 . Therefore, the promotion of GM‐CSF expression observed in the present study might be related to anti‐oxidant pathway.…”
Section: Discussionsupporting
confidence: 67%
“…According to a previous report, an anti‐oxidant, pyrrolidine dithiocarbamate, preventing the degradation of mRNA in cultured pulmonary epithelial cells, increased GM‐CSF expression 23 . It has been demonstrated that the pharmacological effects of Toki and Sai are partly based on their anti‐oxidant action 24,25 . Therefore, the promotion of GM‐CSF expression observed in the present study might be related to anti‐oxidant pathway.…”
Section: Discussionsupporting
confidence: 67%
“…The Japanese traditional remedy Sairei-to, a 12 herb mixture, has shown in human and animal studies to protect the kidney in gentamicin renal toxicity, IgA nephropathy, and lupus nephritis [62]. Another study in rats showed that extracts from the root of the plant Salvia miltiorriza (Danshen) along with fructose 1,6-diphosphate prevented the decline of renal cortical Na-K-ATPase activity induced by ischemia and gentamicin [63].…”
Section: Plant As Nephroprotective Agentsmentioning
confidence: 99%
“…20 These benefits were hypothesized to have been caused by the anti-oxidant actions of ST, 20 given that gentamicin has been shown to exert renal tubular toxicity via enhanced generation of superoxide anion and hydroxyl radical in renal cortical mitochondria. 21 Saireito has similarly proved to be beneficial in a subtotal nephrectomy model of CRF, whereby animals administered 2.5% ST in their food had lower blood pressure, reduced renal damage, decreased protein excretion and greater efferent arteriolar dilation when compared to the untreated rats.…”
Section: Sairei-tomentioning
confidence: 99%